The value of rapport in rangatahi Maori mental health: A Maori social work perspective: a thesis presented in partial fulfilment of the requirements for the degree of Master of Social Work at Massey University, Palmerston North, New Zealand - Mooney, Hannah Aroha (Massey University, 2010)
This thesis examines the rapport building that occurs between rangatahi Māori whaiora (adolescent Māori who use mental health services) and Māori social workers in the field of community mental health. Six Māori social workers were interviewed to explore how they view and practice rapport building with rangatahi Māori whaiora. The Māori social workers were able to provide valuable perspectives based on years of personal and professional experience. The research was conducted using a social constructionist perspective, informed and guided by Māori-centred research principles. A qualitative research method was used and both Massey University and Māori ethical considerations thoroughly explored. Face to face interviews guided by an integrated practice framework, enabled the voices of the Māori social workers to be heard, eliciting in detail where their views have come from. The findings from the research showed that Māori social workers view rapport as essential in their practice and therefore they practice in a way that facilitates this with rangatahi. The social workers utilise their values and beliefs in their practice, according to their worldview; how they were raised; what they have experienced, and what they have learned. Specifically, Māori social workers identified the importance of practicing with a Māori worldview, therefore enabling physical connection, spiritual connection, and cultural connection with the rangatahi. These all contributed towards rapport building with the rangatahi and also their whānau. The importance of action reflection processes were also highlighted. This is due to the balance required from Māori social workers to fulfil the needs of the rangatahi as aligned with their values and beliefs, while meeting the requirements of the organisation, profession and wider community. This thesis explores these key findings.
Keywords: Rangatahi Maori whaiora; Adolescent Maori; Maori social workers; Affinity; Mutual understanding; Rapport; Fields of Research::370000 Studies in Human Society::370200 Social Work::370204 Counselling , welfare and community services